Social network-aware P2P file distribution - Sarmiento, Linda II M.
Several research efforts have shown that knowledge of social relationships between peers in a peer-to-peer system on one hand, and knowledge of the performance of the underlying network, on the other, can independently and separately improve peer-to-peer performance. This study attempts to find out whether the use of both pieces of information simultaneously can bring about greater performance gains. Performance is evaluated in terms of download time as the dominant factor in the perceived end-user performance as file exchange shifted toward larger file sizes and as download request become the majority of the network workload. The proposed solution is an enhanced ISP ranking service which simultaneously considers delay, bandwidth and loss in a simple strategy that limits file sharing within the interest groups. Results show that this provides the lowest short-term and long-term download time when compared to purely random peer selection, or peer selection based on either purely social grouping or on network performance-only. An analysis of storage cost was also provided in order to assess any trade-off as a result of this performance improvement.